2001
DOI: 10.4049/jimmunol.166.6.4124
|View full text |Cite
|
Sign up to set email alerts
|

Different Therapeutic Outcomes in Experimental Allergic Encephalomyelitis Dependant Upon the Mode of Delivery of IL-10: A Comparison of the Effects of Protein, Adenoviral or Retroviral IL-10 Delivery into the Central Nervous System

Abstract: Experimental allergic encephalomyelitis (EAE) is a CNS autoimmune disease mediated by the action of CD4+ T cells, macrophages, and proinflammatory cytokines. IL-10 is a cytokine shown to have many anti-inflammatory properties. Studies have shown both inhibition and exacerbation of EAE after systemic IL-10 protein administration. We have compared the inhibitory effect in EAE of Il10 gene delivery in the CNS. Fibroblasts transduced with retroviral vectors expressing IL-10 could inhibit EAE. This was not associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
74
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 41 publications
3
74
0
Order By: Relevance
“…46 Interestingly, an adenoviral mouse IL-10 (mIL-10) vector, albeit injected at lower titres, was clinically ineffective despite the production of CSF IL-10 levels that compared well with the levels produced by a retroviral cell vector (RCV-mIL-10) that inhibited the severity of clinical signs. 47 The level of infiltration generally correlates with the clinical severity of EAE. 68 Interestingly, in contrast to the prevention of leucocyte accumulation in the CNS that occurs in most other gene therapy studies, RCV-mIL-10-treated animals exhibited significant CNS infiltration but there was a dramatic shift in the phenotype of the infiltration.…”
Section: Local Immunogene Therapy In Cns Autoimmunitymentioning
confidence: 99%
See 4 more Smart Citations
“…46 Interestingly, an adenoviral mouse IL-10 (mIL-10) vector, albeit injected at lower titres, was clinically ineffective despite the production of CSF IL-10 levels that compared well with the levels produced by a retroviral cell vector (RCV-mIL-10) that inhibited the severity of clinical signs. 47 The level of infiltration generally correlates with the clinical severity of EAE. 68 Interestingly, in contrast to the prevention of leucocyte accumulation in the CNS that occurs in most other gene therapy studies, RCV-mIL-10-treated animals exhibited significant CNS infiltration but there was a dramatic shift in the phenotype of the infiltration.…”
Section: Local Immunogene Therapy In Cns Autoimmunitymentioning
confidence: 99%
“…Gene therapy has not yet been attempted in MS, but there have been a number of studies in EAE that have invariably shown some level of efficacy at inhibiting the disease (Table 1), although in many cases this has only been an amelioration rather than elimination of disease. As the majority of the CNS is postmitotic, this puts constraints on the nature of the vector that can be used, and to date administration of plasmid DNA, [32][33][34][35][36][37][38][39][40][41] viral infection, [42][43][44][45][46][47][48][49][50][51][52][53] and retrovirally transduced cell (RVC)-carriers 47,[54][55][56][57][58][59][60][61][62][63] have been investigated in EAE (Table 1). These have largely focused on inhibition of the immune response either applied centrally to target the local pathological events within the CNS or peripherally administered to inhibit: initial sensitization, the activities of circulating cells or perivascular events in areas of local BBB breakdown.…”
Section: Gene Therapy In Autoimmune Demyelinating Diseasementioning
confidence: 99%
See 3 more Smart Citations